Particulate Delivery System Of Chitosan-Diterpene Lactone Fraction Of Sambiloto (Andrographis Paniculata Nees): Preparation, Characterization And In Vitro Drug Release - Retno Sari (Innovare Academic Sciences, 2017)
Objective: This paper was aimed to study the effect of chitosan, sodium tripolyphosphate (TPP) as crosslinker, and diterpene lactone fraction of sambiloto (FDTL) from Andrographis paniculata Nees which contained 75.9% andrographolide on the characteristics of the FDTL-chitosan particulate system. Those characteristics were the physicochemical interaction, physical state, morphology, and drug entrapment efficiency. The in vitro drug release of the selected FDTL-chitosan particulate system was also evaluated.